Association Between Pulse Pressure With All-Cause and Cardiac Mortality in Acute Coronary Syndrome: An Observational Cohort Study - Wang, Man; Su, Wen; Jiang, Chun-Yan; Li, Wei-Ping; Chen, Hui; Li, Hong-Wei (Frontiers in Cardiovascular Medicine, 2022)
Background: Pulse pressure (PP) is a surrogate of aortic stiffness, and reflects cardiac performance and stroke volume. Previous studies have indicated that PP was a robust predictor of cardiovascular outcomes and mortality. However, results have been mixed, and very few studies have focused on the association of PP with mortality in acute coronary syndrome (ACS). Thus, we aimed to investigate the relationship between admission PP and the prognosis of patients with ACS. Methods: This cohort study included 10,824 patients diagnosed with ACS from the Cardiovascular Center Beijing Friendship Hospital Database Bank (CBDBANK) from January 2013 to October 2018. Patients with cardiogenic shock, malignancy, severe trauma and, no PP at admission were excluded. Restricted cubic spline and Cox proportional hazards regression were used to evaluate the association between PP and 1-year all-cause and cardiac mortality. Results: In the whole cohort, a total of 237 (2.19%) all-cause deaths were reported. Restricted cubic spline analysis suggested a J-shaped relationship between PP and mortality. Among patients with ACS, both lower and higher PP levels were related to an increased risk of mortality (P nonlinear < 0.001); with a PP level of 30 or 80 mmHg, as compared with 50 mmHg, the adjusted hazard ratios for 1-year all-cause mortality were 2.02 (95% CI, 1.27 to 3.22) and 1.62 (95% CI, 1.13 to 2.33), respectively, after adjustments for potential confounders. Similar results were observed for cardiac deaths. The J-shaped relationship between PP and mortality remained in a series of subgroup analyses. Conclusions: Our results suggested that both low and high PP were associated with an increased risk of mortality in patients with ACS.